PENGARUH PRODUK, HARGA, PROMOSI DAN PROSES TERHADAP KEPUTUSAN PEMBELIAN ONLINE PADA MASYARAKAT DESA LINGGOSSARI KECAMATAN SUNGAI LILIN - Handayani, Maidiana Astuti; Asiati, Diah Isnaini; Azminudin, Ulul (TECHNOBIZ : International Journal of Business, 2024)
This research aims to determine the influence of products, prices, promotions and processes on online purchasing decisions in the Linggossari Village Community, Sungai Lilin District. The type of research used is associative research. The variables used in this research are product, price, promotion and process as independent variables while purchasing decisions are the dependent variable. The indicators used are 15 indicators. The research population is the Linggossari Village Community, Sungai Lilin District, with a sample size of 100 respondents. The data used is primary data. Probability Sampling . Sampling technique using the Cluster Sampling method. The data collection technique in research is by distributing questionnaires. The data analysis used in this research is multiple linear regression analysis, with a significance level of 10%. The results of the research show that 1) There is a positive and significant influence of Product, Price, Promotion and Process on Purchasing Decisions, 2) There is a positive and significant influence of Product on Purchasing Decisions, 3) There is a positive and significant influence of Price on Purchasing Decisions, 4) there is an influence Positive and significant promotions on Purchasing Decisions. 5) there is a positive and significant influence of the Process on Purchasing Decisions. Keywords: Product, Price, Promotion, Process, and Purchasing Decisions